Alfarería en el proceso identitario del pueblo indígena kukama-kukamiria, centro poblado Santo Tomás, lago Mapacocha-río Nanay 2021 - Rodriguez Vasquez, Keira Luz (2022)
The present investigation, entitled "Pottery in the identity process of the kukama-kukamiria indigenous people, Santo Tomás Population Center, Lake Mapacocha - Nanay River, 2021", was carried out in the district of San Juan Bautista, province of Maynas, department of Loreto. Its main objective is to determine the pottery in the identity process of the populated center linked to the worldview of the kukama-kukamiria indigenous people. The research methodology is qualitative approach, descriptive and ethnographic design. The techniques and instruments applied in the field were the semi-structured interview and participant observation. The study had a population of 23 people who group 15 Kukama families, of which 5 make pottery and 10 are dedicated to the sales network. The results of the investigation show that pottery represents a mark of historical identity manifested in the know-how of pottery that is in relation to their Kukama worldview. The cooked clay pots and their iconos constitute the identity symbol of the Kukama descendants of the populated center as part of the culture and traditional value of their ancestral knowledge recognized at the local, regional, national and international levels.